A Step Towards Stopping the Food Waste Pandemic. The Case of Poland, Slovakia and Czechia - Piekara, Agnieszka (Publishing House of Wroclaw University of Economics and Business, 2024)
In recent years, the awareness surrounding food waste all over Europe, including Poland, Czechia, and Slovakia, has grown, prompting increased efforts to address this issue. The chapter provides an overview of the food waste and loss landscape in these countries, shedding light on the scale of the problem, its underlying causes, and the initiatives undertaken to combat it. By understanding each country’s challenges and opportunities, stakeholders can develop targeted strategies to minimise food waste and promote more sustainable food systems.
Piekara, A. (2024). A Step Towards Stopping the Food Waste Pandemic. The Case of Poland, Slovakia and Czechia. In B. Drelich-Skulska, M. Sobocińska, & A. Tomášková (Eds.), The Importance of Universities for Society and Economy. The Experience of Researchers from the Visegrád Group (pp. 59-67). Publishing House of Wroclaw University of Economics and Business.
Keywords: food waste; food losses; food waste pandemic; food waste in CEE countries